Modeling the intermixing effects in highly strained asymmetric InGaAs/GaAs quantum well - Souaf, M.; Baira, M.; Maaref, H.; Ilahi, B. (Condensed Matter Physics, 2015)
In this work, we have theoretically investigated the intermixing effect in highly strained In₀.₃Ga₀.₇As/GaAs QW taking into consideration the composition profile change resulting from in-situ indium surface segregation. To study the impact of the segregation effects on the postgrowth intermixing, one dimensional steady state Schrodinger equation and Fick's second law of diffusion have been numerically solved by using the finite difference methods. The impact of the In/Ga interdiffusion on the QW emission energy is considered for different In segregation coefficient. Our results show that the intermixed QW emission energy is strongly dependent on the segregation effects. The interdiffusion enhanced energy shift is found to be considerably reduced for higher segregation coefficients. This work adds considerable insight into the understanding and modeling of the effects of interdiffusion in semiconductor nanostructures. У данiй роботi ми теоретично дослiдили ефект взаємного перемiшування у сильнонапруженiй квантовiй
ямi In₀.₃Ga₀.₇As/GaAs, беручи до уваги змiну концентрацiйного профiлю в результатi in-situ поверхневої сегрегацiї iндiю. З метою вивчення впливу ефектiв сегрегацiї на взаємне перемiшування в пiсляростовий перiод, чисельно розв’язанi одновимiрне рiвняння Шредiнгера в стацiонарному режимi i другий
закон дифузiї Фiка, використовуючи методи скiнчених рiзниць. Розглянуто вплив взаємної дифузiї In/Ga
на енергiю емiсiї квантової ями для рiзних коефiцiєнтiв сегрегацiї iндiю. Нашi результати показують, що
енергiя емiсiї взаємноперемiшаних квантових ям сильно залежить вiд ефектiв сегрегацiї. Виявлено, що
пiдсилений взаємною дифузiєю енергетичний зсув значно зменшується для вищих коефiцiєнтiв сегрегацiї. Ця робота значно поглиблює розумiння та моделювання ефектiв взаємної дифузiї у напiвпровiдникових наноструктурах.